Groundwater Resources in Moroccan Coastal Aquifers: Insights of Salinization Impact on Agriculture - Ez-zaouy, Y.; Bouchaou, L.; Saad, A.; Hssaisoune, M.; Brouziyne, Youssef; Dhiba, D.; Chehbouni, Abdelghani (MDPI, 2022)
Across several coastal areas in Morocco, groundwater is the strategic source of irrigation. In this work, a database of thirteen Moroccan coastal aquifers was used to assess groundwater for agriculture purposes, as well as to highlight the process responsible of the degradation of groundwater resource quality in Moroccan coastal areas. According to electrical conductivity parameter, the results show that 92% of the collected samples were not suitable for irrigation uses. This situation is due to seawater intrusion and water–rock interaction processes, in addition to intensive agriculture activities and the introduction of domestic and industrial wastewater without any treatment. In order to control the impact of groundwater salinity on agriculture, management plans are proposed.